The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.celrep.2013.01.012
|View full text |Cite
|
Sign up to set email alerts
|

RP58 Regulates the Multipolar-Bipolar Transition of Newborn Neurons in the Developing Cerebral Cortex

Abstract: Accumulating evidence suggests that many brain diseases are associated with defects in neuronal migration, suggesting that this step of neurogenesis is critical for brain organization. However, the molecular mechanisms underlying neuronal migration remain largely unknown. Here, we identified the zinc-finger transcriptional repressor RP58 as a key regulator of neuronal migration via multipolar-to-bipolar transition. RP58(-/-) neurons exhibited severe defects in the formation of leading processes and never shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 40 publications
3
88
1
Order By: Relevance
“…The multipolar-to-bipolar transition is a critical event of the radial migration process (Tabata and Nakajima, 2003;Kriegstein and Noctor, 2004;LoTurco and Bai, 2006) that is regulated by a multitude of signaling molecules (Jossin and Cooper, 2011;Chen et al, 2008;Miyoshi and Fishell, 2012;Xie et al, 2013;Nagano et al, 2004;Ohshima et al, 2007;Westerlund et al, 2011;Heng et al, 2008;Bai et al, 2003;Ohtaka-Maruyama et al, 2013). The large majority of late-generated pyramidal precursors are generated from unpolarized intermediate progenitors (TBR2 positive cells) and inherit multipolar morphologies with highly dynamic processes (Kriegstein and Alvarez-Buylla, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…The multipolar-to-bipolar transition is a critical event of the radial migration process (Tabata and Nakajima, 2003;Kriegstein and Noctor, 2004;LoTurco and Bai, 2006) that is regulated by a multitude of signaling molecules (Jossin and Cooper, 2011;Chen et al, 2008;Miyoshi and Fishell, 2012;Xie et al, 2013;Nagano et al, 2004;Ohshima et al, 2007;Westerlund et al, 2011;Heng et al, 2008;Bai et al, 2003;Ohtaka-Maruyama et al, 2013). The large majority of late-generated pyramidal precursors are generated from unpolarized intermediate progenitors (TBR2 positive cells) and inherit multipolar morphologies with highly dynamic processes (Kriegstein and Alvarez-Buylla, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Subsequently, they transform from a multipolar to a bipolar morphology that is suitable for locomotion along the radial glial fibers before entering the subplate (SP) and CP (Rakic, 1972;Nadarajah et al, 2001). Recently, the importance of the multipolar migratory phase involved in mature cortical network assembly has received substantial attention (LoTurco and Bai, 2006;Torii et al, 2009;Costa and Hedin-Pereira, 2010;Yamagishi et al, 2011;Miyoshi and Fishell, 2012;Ohtaka-Maruyama et al, 2013;Inoue et al, 2014). The early postmitotic neuronal marker NeuroD1 is highly localized to MAZ (Tabata et al, 2009(Tabata et al, , 2012(Tabata et al, , 2013, and downregulation of NeuroD1 in the early multipolar phase enables cells to initiate Unc5D (a marker for late multipolar cells) expression, which facilitates their transition from the early to the late multipolar phase ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that these genes are deleted in our index patient. In support for the neuronal functions for AKT3 and ZNF238, studies in mice have demonstrated their critical roles in neurogenesis, neuronal migration, and the formation of the brain [Okado et al, 2009;Poduri et al, 2012;Ohtaka-Maruyama et al, 2013;Heng et al, 2015]. Also, whole exome sequencing studies have revealed that abnormalities in brain growth are associated with point mutations to AKT3 [Lee et al, 2012;Riviere et al, 2012] and ZNF238 [Rauch et al, 2012;de Munnik et al, 2014].…”
Section: Reinforcing the Association Between 1q43-q44mentioning
confidence: 97%